HUBUNGAN ANTARA SENSITISASI ALERGEN INDOOR DENGAN KEKAMBUHAN ASMA PADA ANAK - , Agus Tusino; , dr. Sumadjono, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Prevalence of asthma in children vary in some areas. Inhalan allergen exposure may plays causative role in the development of asthma, persistent asthma and lung function. Avoidance of allergens plays an important role in management of atopy asthma especially indoor allergens, because most of school-age children activities are in the house. This study aim to examine relationship between indoor allergens and asthma reattack in children aged 6 to <18 years old. A cross sectional study was carried out in children with asthma aged 6 to <18 years old who visited to pediatric clinic or emergency room of Sardjito General Hospital. Subjects was undergone skin prick test to indoor allergens, those are dust mites, cockcroach, cat, dog, and mold. Prevalence ratio (PR) analysis was done to know the relationship between indoor allergens and asthma reattack in children. Sixty-eight children with asthma aged 6 to <18 years old were enrolled and analyzed. PR of sensitization of indoor allergen to asthma reattack is 3,770, with confidence interval (CI) 95% (1,425-9,972) and p=0.002. PR of sensitization of dust mite allergen to asthma reattack is 4,773, with CI 95% (1,803-12,634) and p=0.001. PR of sensitization of cockroach allergen to asthma reattack is 3,333, with CI 95% (1,752-6,343) and p=0.001. PR of sensitization of cat allergen to asthma reattack is 2,175, with CI 95% (1,129-4,190) and p=0.066. PR of sensitization of dog allergen to asthma reattack is 3,039, with CI 95% (1,770- 5,218) and p=0.012. PR of sensitization of mold allergen to asthma reattack is 3,500, with CI 95% (2,101-5,832) and p=0.001. In conclusion, most of indoor allergens sensitization have relationship with asthma reattack in children.